EXTH-60. PRECLINICAL STUDY OF PAMIPARIB, A CNS-PENETRANT PARP INHIBITOR, IN IDH1/2 MUTATED GLIOMAS. (12th November 2021) - Hong, Christopher; Sundaram, Ranjini; Bindra, Ranjit
Abstract: Our group has demonstrated that IDH1/2 mutated gliomas harbor intrinsic homologous recombination (HR) defects mediated by the oncometabolite, 2-HG, rendering them sensitive to PARP inhibitors. Here, we studied the efficacy of pamiparib, a CNS-penetrant PARP inhibitor with potent PARP trapping ability, in combination with temozolomide (TMZ) and radiation therapy (RT) in IDH1/2 mutated gliomas. We also studied the pharmacokinetics of BGB290 to demonstrate CNS penetrance. We performed a series of DNA repair functional studies with in vitro short- and long-term viability assays, as well as in vivo studies utilizing an orthotopically injected rat glioma model with bioluminescence. Pharmacokinetics was measured with a previously validated LCMS/MS technique. Short-term and long-term viability assays in paired isogenic IDH1 wildtype and mutant cell lines showed the IDH1 mutation conferred enhanced sensitivity to pamiparib with several-fold decreases in IC50, as well as TMZ and RT as expected. Combination treatment with pamiparib and TMZ or RT also demonstrated synergistic interactions in these same cell lines, dependent upon IDH1 mutation status. An ELISA assay confirmed PARylation inhibition by pamiparib at the nanomolar range in a dose-dependent manner. Pharmacokinetic analysis demonstrated favorable CNS penetration with tumor:plasma ratios ( >0.20) observed with low (3 mg/kg) and high (6 mg/kg) doses of pamiparib, orally administered BID to rats harboring intrinsic rat glioma intracranial tumors. These levels persisted between 2 and 8 hours after last dosing. Pamiparib also selectively penetrated tumors over normal brain with normal brain:plasma ratios under 0.20. These data suggest pamiparib may selectively target IDH1/2 mutated gliomas and act synergistically with TMZ and RT to exploit intrinsic HR defects associated with these tumors. Pharmacokinetic analysis suggest favorable CNS penetration after standard bid oral administration. As such, these results lay the groundwork for study of pamiparib with TMZ and/or RT in patients with IDH1/2 mutated gliomas.